Liar’s Domination in Sun Graphs - Shanthi, AS; Thomas, Diana Grace (International Journal of Computer Sciences and Engineering, 2025)
Liar`s dominating set is one that identifies an intruder`s location even if one device in the neighborhood of the intruder vertex becomes faulty, that is, any one device in the neighborhood of the intruder vertex can misidentify any vertex in its closed neighborhood as the location of the intruder. The liar’s domination number is the minimum cardinality of a liar’s dominating set. In this paper, we determine the liar’s domination number for sun graphs, sun let graphs, line graphs of sun let graphs and wheel graphs.